Analisis Implementasi Gadai Emas Pada Bank Syariah Indonesia Ditinjau Dari Shariah Compliance - Andi Hotmatua Harahap; Atika Atika (Journal Of Business, Finance, and Economics (JBFE), 2024)
The practice of Pawning Gold is currently widely carried out by Indonesian Sharia Banks. One of the Islamic Bank products that uses sharia principles as a guideline in its operations, the level of compliance with sharia compliance in its implementation must be measured and adjusted to sharia compliance. This research is a benchmark for the level of sharia compliance in the implementation of BSI gold pawning. Researchers chose BSI KCP Medan Marelan as the research object with a research focus related to the suitability of Sharia Compliance in the implementation of gold pawning at BSI. This research uses a qualitative approach method with a case study type. The research results show that the BSI KCP Medan Marelan gold pawn uses three contracts, namely, the rahn, qardh and ijarah contracts, each of which is guided by the DSN-MUI fatwa, which in the DSN fatwa is emphasized regarding the implementation of each contract and the ujroh fee is charged to the customer. Regarding the implementation of gold pawning at BSI, starting from the contract, collateral, maintenance costs, until the end of the contract, it is carried out in accordance with sharia principles based on the DSN-MUI fatwa.